The new paradigm for financial markets : the credit crisis of 2008 and what it means - Soros, George, 1930- (New York : PublicAffairs, 2008)
In the midst of the most serious financial upheaval since the Great Depression, legendary financier George Soros explores the origins of the crisis and its implications for the future. In a concise essay that combines practical insight with philosophical depth, Soros makes an invaluable contribution to our understanding of the great credit crisis and its implications for our nation and the world.
Introduction -- Setting the stage -- The core idea -- Autobiography of a failed philosopher -- The theory of reflexivity -- Reflexivity in financial markets -- The super-bubble hypothesis -- Autobiography of a successful speculator -- My outlook for 2008 -- Some policy recommendations.
Includes bibliographical references.
HU OSA 208 - Donation of the Open Society Institute-New York
Keywords: Financial crises -- United States; Credit -- United States; United States -- Economic policy; United States -- Economic conditions -- 21st century